Psicologia como retórica : uma análise das apropriações dos conceitos vigotskianos pelo construcionismo social - Costa, Eduardo Moura da (2015)
In the present study, with theoretical-methodological and conceptual nature, the objective is to analyze the conceptions of the Soviet psychologist Lev Semenovich Vygotsky that were appropriated by the social constructionism, a cultural movement that, in recent decades, has penetrated into various fields of knowledge, including Psychology. The constructionist presupposition is that the knowledge, both the human and the natural phenomena, is a social construction, created and maintained by the needs of each community. The truth would not have secure supports in reality, but their access would be possible only in groups that create them. The man himself would be a social construction, that would develop in relation to the other, mediated by language. The hypothesis of this work is that by appropriating concepts of Vygotsky, the authors displace them from their conceptual system, whose root are in the historical and dialectical materialist method. This research goes in the opposite direction of postmodern relativism, which cares little about the philosophical and methodological consistency of theories, even less with the praxis, that is, coordination between interpretation and transformation of reality. To achieve the proposed objectives, This study was separated into three sections. The first is dedicated to the social constructionism. Analyzes the historical context in which it originated, their main assumptions, the theoretical background and some of the main criticisms to this movement in psychology. The second section it presents the Historical and Cultural Psychology of Vygotsky, returning to its basic premises to check if the constructionism it is faithful to them. Finally, the last section, it is a counterpoint between the two visions analyzed. Presents the rhetorical-responsive version of constructionism and address both - the way in which Vygotsky is appropriate as the limits of that interpretation. Finally, we analyzes the inconsistencies presented in the appropriation of Vygotsky's concepts, identifying them as the basic problem of this world view. The key to this problem would be the idealized conception of language in which this would be independent of the material reproduction of society. In addition, much of the constructionists, in a deliberately way or not ,confound the form of acquisition of knowledge with the object to be known. For dialectical materialism, methodological basis of Vygotskyan psychology, scientific knowledge is mediated by the language, the social practices and the natural and social phenomena; it is not therefore a purely linguistic construction. This way, the production of knowledge follows the form of material reproduction of society, the shape of the work, developed over complex historical and social processes. It concludes that the constructionist conception is in disagreement with the proposals of Vygotsky: his theoretical framework can not be incorporated into this movement unless it is taken off from its conceptual system and its philosophical and methodological basis.